Characteristics and outcome of patients with acute myeloid leukaemia and t(8;16)(p11;p13): results from an International Collaborative Study. (2nd February 2021) - Kayser, Sabine; Hills, Robert K.; Langova, Ralitsa; Kramer, Michael; Guijarro, Francesca; Sustkova, Zuzana; Estey, Elihu H.; Shaw, Carole M.; Ráčil, Zdeněk; Mayer, Jiri; Zak, Pavel; Baer, Maria R.; et al.
Summary: In acute myeloid leukaemia (AML) t(8;16)(p11;p13)/ MYST3–CREBBP is a very rare abnormality. Previous small series suggested poor outcome. We report on 59 patients with t(8;16) within an international, collaborative study. Median age was 52 (range: 16–75) years. AML was de novo in 58%, therapy‐related (t‐AML) in 37% and secondary after myelodysplastic syndrome (s‐AML) in 5%. Cytogenetics revealed a complex karyotype in 43%. Besides MYST3–CREBBP, whole‐genome sequencing on a subset of 10 patients revealed recurrent mutations in ASXL1, BRD3, FLT3, MLH1, POLG, TP53, SAMD4B ( n  = 3, each), EYS, KRTAP9‐1 SPTBN5 ( n  = 4, each), RUNX1 and TET2 ( n  = 2, each). Complete remission after intensive chemotherapy was achieved in 84%. Median follow‐up was 5·48 years; five‐year survival rate was 17%. Patients with s‐/t‐AML ( P  = 0·01) and those with complex karyotype ( P  = 0·04) had an inferior prognosis. Allogeneic haematopoietic cell transplantation (allo‐HCT) was performed in 21 (36%) patients, including 15 in first complete remission (CR1). Allo‐HCT in CR1 significantly improved survival ( P  = 0·04); multivariable analysis revealed that allo‐HCT in CR1 was effective in de novo AML but not in patients with s‐AML/t‐AML and less in patients exhibiting a complex karyotype. In summary, outcomes of patients with t(8;16) are dismal with chemotherapy, and may be substantially improved with allo‐HCT performed in CR1.